An ergonomic and safty evaluation of footwear used by male industrial workers in Nigeria: a case study (2007)
This study focuses on footwear used by Nigerian industrial workers. The suitability and comfort ability of these shoes used in a typical Nigerian factory were assessed based on their response to some well-structured questionnaire. Some important features of the shoes were compared with internationally recommended standards. The result shows that 62% of the respondents' shoes are suitable. These are mostly shoes that are light weight, low heeled made of leather material and steel toed, though some of them are not steel toed. When compared with the standard features and characteristics, it is observed that about 60% complies with the Internationally accepted standards of EN 345, EN 346 and EN347 for safety shoes, protective shoes and work shoes respectively.